2014
DOI: 10.5897/ajfs2013.1114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boiling and frying on nutritional value and in vitro digestibility of rabbit meat

Abstract: Effect of boiling and frying on nutritional value and in vitro digestibility of rabbit meat were investigated. It was observed that boiling for 15 min increased the digestibility and nutritional value of rabbit meat, while boiling for 5 and 40 min led to their loss. Although, frying for 2 and 4 min produced an acceptable digestibility and nutritional value, the values were lower than those of the boiled rabbit meats. These results were supported by the analysis of amino acid and SDS-PAGE. Boiling or frying for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 51 publications
4
7
3
Order By: Relevance
“…The protein content decreased with the increases in the temperature and time and differed significantly (p < .05) with all the samples studied. These results showed similar trend with the work ofZhang, Wang, Wang, and Zhang (2014) who confirmed that frying time had considerable decrease in the protein content of fried rabbit meat.…”
supporting
confidence: 90%
“…The protein content decreased with the increases in the temperature and time and differed significantly (p < .05) with all the samples studied. These results showed similar trend with the work ofZhang, Wang, Wang, and Zhang (2014) who confirmed that frying time had considerable decrease in the protein content of fried rabbit meat.…”
supporting
confidence: 90%
“…On the microbiological aspect, these low moisture contents could limit the development of microorganisms [18]. The effect of moisture content increase observed during scalding in this study is contrary to the works of [19] who found that boiling of rabbit meat for 5, 15 and 40 min enhanced the reduction of the water content by 12.03%, 11.66% and 12.98% respectively. This difference can be explained by the structure of proteins and their capacity to absorb and retain water.…”
Section: Cookingcontrasting
confidence: 91%
“…Murphy and Marks [33] also reported an increase in protein degradation of ground chicken patties at boiling temperature (80°C). Zhang et al [34] also reported an increase in degradation of rabbit meat proteins with an increase in treatment time, however, they reported greater degradation in fried samples, which can be due to differences in cooking methodology (wet vs dry) and samples used. The higher protein degradation in boiled camel meat correlates well with the lower hardness values in the TPA (Table 2).…”
Section: Protein Pattern As Detected By Sodium Dodecyl Sulphate-polya...mentioning
confidence: 94%